"TEACHING FINE ARTS EDUCATION METHODOLOGY" (Conferencea, 2023)
Children will learn about the lifestyle, culture, clothing, and working tools of our ancestors who lived thousands of years ago, based on the observation of historical, batal genre paintings and illustrations of literary works. They will have an idea about the structure, shape, color, dimensions of the buildings, plants, animals, objects of that time. As you know, children, it is historical. They will have a lot of knowledge about historical events, battles, people's lives, animals, urban and natural landscapes, working in battle, landscape, life, still life, animal, legendary genres.